Implementation of the Minimum Service Standards Policy in the Social Sector in Gorontalo Province - Wahyudi Gobel (West Science Social and Humanities Studies, 2026)
This study aims to analyze the implementation of the Minimum Service Standards (MSS) policy in the social sector in Gorontalo Province and identify factors influencing its effectiveness. The study used a qualitative approach with a case study design, using data collection techniques such as in-depth interviews, observation, and document analysis. Data analysis was conducted thematically with reference to the policy implementation model, specifically the variables of communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of the MSS in the social sector in Gorontalo Province is not yet fully optimal, characterized by fluctuating service outcomes and not consistently meeting quality standards. The main factors influencing implementation include limited resources (budget, human resources, and infrastructure), ineffective cross-sector communication and coordination, and obstacles within the bureaucratic structure. However, the relatively high disposition of implementers is a supporting factor in maintaining the sustainability of program implementation. In addition, external conditions such as economic, social, and political factors also influence the effectiveness of policy implementation. This study contributes theoretically by strengthening the relevance of the policy implementation model in the context of regional social services, and empirically provides an overview of the dynamics of MSS implementation in Eastern Indonesia. Practically, the results of this study recommend strengthening institutional capacity, improving the quality of resources, and strengthening cross-sector coordination to increase the effectiveness of policy implementation.